Women’s hair in Lager narratives - Czarnecka, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article offers an analysis of women’s Lager narratives in which the procedure of removing hair from female prisoners of concentration camps was reflected. It indicates the procedure’s cultural, social, and psychological meanings presenting it as an element of the extensive camp strategy of violence, a ritual of downgrading, and a form of violating a woman’s identity and intimacy. By presenting various circumstances in which women were shaved in the camps, it also indicates the situation-based complexity of the camp experience, its various stages, and contexts. The text refers to various sources, and considers the experiences of women of various nationalities, e.g. Germans, Poles, and Jews.